The Effectiveness of Adding Immunostimulants, Probiotics, and Liming Methods on Water Quality and Productivity of Shrimp Litopenaeus vannamei in Dewi Laut Aquaculture Company, Garut, Indonesia - Permatasari, Sheny; Firdausi, Amalia Putri; Pradian, Yassar Ariq; Sopacua, Ivana Oktarina (Research and Social Study Institute, 2025)
Background: The whitelegs shrimp Litopenaeus vannamei is one of Indonesia's leading commodities. However, Intensive culture of Litopenaeus vannamei faces challenges such as environmental stress and decreased productivity due to fluctuating water quality.Aims & Methods: This study aimed to evaluate the effectiveness of adding immunostimulants (vitamin-mineral mix and garlic extract at 2 ppm), probiotics (2 ppm every two weeks), and lime treatment (CaO at 10 ppm) on water quality and the productivity of L. vannamei in ponds at PT. Dewi Laut Aquaculture, Garut. The observed productivity parameters included Average Body Weight (ABW), population, biomass, Feed Conversion Ratio (FCR), Survival Rate (SR), and size. Meanwhile, the measured water quality parameters included physical parameter such as temperature, chemical parameters such as pH, dissolved oxygen (DO), total ammonia nitrogen (TAN), total alkalinity, and total organic matter (TOM), as well as biological parameters such as total phytoplankton, total bacteria count (TBC), and total vibrio count (TVC).Result: The results showed that the applied treatments produced good culture performance, with ABW reaching 13.37 grams, SR at 91.01%, FCR at 1.7 and productivity of 20.39 tons/ha. Meanwhile, water quality monitoring indicated that some parameters exceeded the ideal ranges for shrimp culture, such as pH (maximum 9.12), TOM (up to 134 ppm), and TAN (up to 2.6 ppm). However, there is synergy between probiotics and immunostimulants, these conditions were still tolerable for the shrimp.